Pengaruh Rekrutmen, Pengembangan Karir, Dan Pelatihan Terhadap Kepuasan Kerja (Studi Kasus pada Karyawan PT Sembilan Puluh Enam Derajat di Jakarta Selatan) - Aris, Aris Wahyu Kuncoro; Maruji Pakpahan; Hasan Ipmawan; Dwi Kristanto; Koen Hendrawan; Jesshinta Wendy Sari (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to determine the effect of Recruitment, Career Development, and Training on Job Satisfaction. Using the Non Probability Sampling technique using the saturation method. The population in this study were 87 employees of PT Ninety Six Degrees (Flash Coffee) South Jakarta. This research was conducted using multiple linear regression methods assisted by the SPSS version 25 program and Microsoft Excel 2016. The results showed that Recruitment (X1) had a significant effect on Job Satisfaction (Y), Career Development (X2) had a significant effect on Job Satisfaction (Y), and Training (X3) has a significant effect on Job Satisfaction (Y).